A Cut-off low at 500 hPa Geopotential Height and Rainfall Events over Iraq: Case Studies - Mohammed Abdul Raheem Jabbar; Ahmad S. Hassan (Iraqi Journal of Physics, 2022)
A cut-off low is a closed low with a low value of geopotential height at the upper atmospheric levels that has been fully detached (cut-off) from the westerly flow and move independently. A cut-off low causes extreme rainfall events in the mid-latitudes regions. The main aim of this paper is to investigate the cut-off low at 500 hPa over Iraq from a synoptic point of view and the behavior of geopotential height at 500 hPa. To examine the association of the cut-off low at 500 hPa with rainfall events across Iraq, two case studies of heavy rainfall events from different times were conducted. The results showed that the cut-off low at 500 hPa with a low value of geopotential height will strengthen the low-pressure system at the surface, leading to a case of atmospheric instability over Iraq and a significant amount of rain will fall if the moisture is available.